Measuring Illegal Activity and the Effects of Regulatory Innovation: Tax Evasion and the Dyeing of Untaxed Diesel - Marion, Justin; Muehlegger, Erich (Journal of Political Economy, 2008)
This article examines tax evasion in the diesel fuel market. Diesel fuel used for on‐road purposes is taxed, while other uses are untaxed, creating an incentive for firms and individuals to evade on‐road diesel taxes by purchasing untaxed diesel fuel and then using it for on‐road use. We examine the effects of a federal regulatory innovation in October 1993, the addition of red dye to untaxed diesel fuel at the point of distribution, which significantly lowered the cost of regulatory enforcement. We find that sales of diesel fuel rose 26 percent following the regulatory change, while sales of heating oil, which is an untaxed perfect substitute, fell by a similar amount. The effect on sales was higher in states with higher tax rates and in states likely to have higher audit costs. We also find evidence that heating oil sales were less responsive to demand factors, such as temperature, prior to the dye program, indicating that a significant fraction of predye sales was illegitimate. Furthermore, we find a pattern of price and tax elasticities consistent with innovation in new evasion techniques subsequent to the regulatory change. Finally, we estimate that the elasticity of tax revenues with respect to the tax rate was 0.60 prior to the dye program yet would have been 0.85 in the absence of evasion.